Fermented broccoli stalk by-product with lactic acid bacteria ameliorates high-fat diet-induced obesity in C57BL/6 mice - Jiang, Lihao; Wu, Qinghang; Lu, Zhiyi; Zhang, Jianming; Zhao, Dandan; Liu, Daqun; Zhang, Chengcheng (Frontiers in Nutrition, 2025)
IntroductionLactic acid bacteria (LAB) fermentation of broccoli stem by-product (BsBP) has been shown to enhance the accumulation of bioactive isothiocyanates, thereby possessing the potential as an anti-obesity functional food. However, the obesity-alleviating effects of fermented BsBP with LAB have not been extensively studied.MethodsIn this study, BsBPs were fermented by a single strain of Lacticaseibacillus casei YC5 or Pediococcus pentosaceus RBHZ36, and their impact on obesity-alleviating was investigated in C57BL/6 mice subjected to a high-fat diet (HFD).Results and discussionFermented BsBP intervention markedly limited body weight gain and adipose coefficients, improved serum lipid profiles and glucose levels, and reduced hepatic levels of ALT, AST, and the pro-inflammatory cytokine TNF-α in these mice. Fermented BsBP with LAB exhibited more effective anti-obesity effects than fresh BsBP in HFD-fed mice. Furthermore, supplementation with fermented BsBP modulated the gut microbial imbalance induced by an HFD, enhancing both microbial diversity and richness. This intervention promoted the proliferation of health-associated bacterial genera such as Akkermansia and Bacteroides while concurrently reducing the abundance of taxa linked to obesity, including Colidextribacter, Helicobacter, and Mucispirillum. Predictive analysis of microbial function indicated that alterations in the gut microbiota were linked to enhanced energy metabolism and activation of the PPAR signaling pathway. Collectively, this study highlighted that BsBP fermented with LAB has the potential to be a functional food for obesity management.